Effects of a Mindfulness-Based Intervention on Event-Related Potentials (P3) and Depressive Symptoms in Oncological Patients - Theresa Schweig MD; Madeleine Fink PHD; Kira Schmidt MSc; Marvin Krawutschke MD; Saskia Pasche MSc; Eva-Maria Skoda MD; Martin Teufel MD; Bernhard W. Müller PhD (Integrative Cancer Therapies)
Objective: The aim of this study was to investigate changes in P3 amplitude and latency to emotional stimuli with different arousal and valence levels after a mindfulness-based intervention in oncological patients. Methods: P3 amplitude and latency at Fz, Cz, and Pz to emotional salient stimuli differing in valence (positive vs. negative) and arousal (low vs. high) levels were measured in 17 oncological patients ( M age  = 51 years, SD = 9.17, females = 11) before and after a mindfulness-based intervention in a waitlist-controlled clinical trial. Group sessions were held 2x/week over a period of 5 weeks. Results: Arousal and valence levels of emotional salient stimuli were significant modulators of P3 amplitudes ( P  = .050; P  = .006, respectively). P3 amplitudes at Fz decreased significantly from pre-waitlist to post-intervention ( P  = .002). P3 latency for negatively valenced stimuli decreased from pre- to post-intervention with trending significance ( P  = .080). P3 latency at Pz showed a trend of being shorter than P3 latency at Cz ( P  = .066). Depressive symptoms showed a decreasing trend from pre- to post-treatment ( P  = .075). Conclusions: We could show that arousal and valence levels of emotional salient stimuli are important modulators of P3 amplitudes and latencies in oncological patients. P3 amplitudes at Fz decreased significantly from pre-waitlist until after mindfulness-based intervention, decreases from pre-to post-intervention were linear, but not significant. In oncological patients the mindfulness-based intervention seems to have its strongest effect on the frontal electrode Fz, not the electrode Pz where its amplitude was largest. Depressive symptoms could be reduced.